2023
DOI: 10.1021/jacs.3c04734
|View full text |Cite
|
Sign up to set email alerts
|

3D Covalent Organic Framework as a Metastable Intermediate in the Formation of a Double-Stranded Helical Covalent Polymer

Abstract: The design and development of intricate artificial architectures have been pursued for decades. Helical covalent polymer (HCP) was recently reported as an unexpected topology that consists of chiral 1D polymers assembled through weak hydrogen bonds from achiral building blocks. However, many questions remained about the formation, driving force, and the single-handedness observed in each crystal. In this work, we reveal a metastable, racemic, fully covalently cross-linked, 3D covalent organic framework (COF) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Subsequently, the reaction was heated at 120 °C for 30 days. The formation of HCP−Na follows an intermediate srs‐phase, as previously reported (Figure S1) [20] . Notably, the srs‐phase persists more when using alternative solvent systems, such as 1 : 2 acetonitrile/mesitylene or boric acid as the boron source (Table S1).…”
Section: Figuresupporting
confidence: 80%
See 3 more Smart Citations
“…Subsequently, the reaction was heated at 120 °C for 30 days. The formation of HCP−Na follows an intermediate srs‐phase, as previously reported (Figure S1) [20] . Notably, the srs‐phase persists more when using alternative solvent systems, such as 1 : 2 acetonitrile/mesitylene or boric acid as the boron source (Table S1).…”
Section: Figuresupporting
confidence: 80%
“…The dynamic nature of the bonds enables error correction as a thermodynamic control to favor the formation of structures that represent thermodynamic minimums. There is great interest in further understanding the factors that lead to certain structures being more thermodynamically favorable and the equilibrium between polymetric phases [17–22] . Additionally, it has been demonstrated that minor changes to the structure, such as larger counter‐ions or the introduction of steric interactions, can change the interpenetration, stacking between layers, and topology [23–27] .…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…2D COFs constructed by monomers with varied geometries and symmetries adopt different topological networks such as hexagonal, rhombic, Kagome, etc. In addition, there have been reports about helical COFs whose structures are more complex and unique, which expands the properties and functionalities of COF materials. As we know, the properties and potential applications of COFs are dependent not only on their intralayer linkage and network topology but also on the interlayer interactions and stacking mode. Herein, we report a highly crystalline helical COF material with a rod-like morphology, termed helical-COF TP‑Py , in which neighboring layers stack in a rotational manner with respect to one another, leading to a helical morphology clearly discernible under scanning electron microscopy (SEM) observation.…”
Section: Introductionmentioning
confidence: 99%